Analyzing the Impact of Packaging Design on Consumer Purchasing Decisions in the Cosmetics Industry - Sitopu, Joni Wilson; Firdaus, Adhy (IHSA Institute, 2024)
This study examines the influence of product packaging on consumer purchasing decisions in the cosmetics industry, aiming to understand how various packaging elements impact consumer behavior. Utilizing a mixed-methods approach, including quantitative surveys, qualitative focus groups, and observational studies, the research provides comprehensive insights into consumer preferences and the role of packaging in shaping purchasing decisions. Key findings indicate that aesthetic appeal, functional design, brand congruence, and sustainability are critical factors influencing consumer choices. Visually attractive and modern packaging designs significantly enhance purchase intent, while functional elements such as ease of use and convenience improve consumer satisfaction and loyalty. Consistent alignment between packaging and brand identity fosters trust and loyalty, and sustainability features appeal to eco-conscious consumers. Emotional engagement through packaging also plays a pivotal role in creating lasting consumer connections. The study's practical implications suggest that cosmetic companies should invest in innovative, functional, and sustainable packaging designs that align with their brand identity to attract and retain consumers.